Brooding Is Related to Neural Alterations during Autobiographical Memory Retrieval in Aging - Schneider, Sophia; Brassen, Stefanie (Frontiers in Aging Neuroscience, 2016)
Brooding rumination is considered a central aspect of depression in midlife. As older people tend to review their past, rumination tendency might be particularly crucial in late life since it might hinder older adults to adequately evaluate previous events. We scanned 22 non-depressed older adults with varying degrees of brooding tendency with functional magnetic resonance imaging while they performed the construction and elaboration of autobiographical memories. Behavioral findings demonstrate that brooders reported lower mood states, needed more time for memory construction and rated their memories as less detailed and less positive. On the neural level, brooding tendency was related to increased amygdala activation during the search for specific memories and reduced engagement of cortical networks during elaboration. Moreover, coupling patterns of the subgenual cingulate cortex with the hippocampus and the amygdala predicted details and less positive valence of memories in brooders. Our findings support the hypothesis that ruminative thinking interferes with the search for specific memories while facilitating the uncontrolled retrieval of negatively biased self-schemes. The observed neurobehavioral dysfunctions might put older people with brooding tendency at high risk for becoming depressed when reviewing their past. Training of autobiographical memory ability might therefore be a promising approach to increase resilience against depression in late-life.